2013
DOI: 10.1111/jgh.12428
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nonalcoholic fatty liver disease in mainland of China: A meta‐analysis of published studies

Abstract: The prevalence of NAFLD is lower than the estimates from developed countries. But it still reaches the epidemic proportions, and its prevalence is increasing. Meanwhile, a nationwide prevalence investigation should be conducted to confirm the estimates and determine more accurate rates for specific populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
157
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(166 citation statements)
references
References 23 publications
8
157
1
Order By: Relevance
“…The prevalence of non-alcoholic fatty liver disease (NAFLD) in the general population is growing worldwide: 44% in the USA, 33% in Europe and 25% in Italy [1][2][3][4][5][6]; for non-alcoholic steatohepatitis (NASH), the progressive form of NAFLD, the estimate is 2-3% [3,5]. A large cohort study reported that NAFLD was associated with 26% higher 5-year overall health-care costs, mainly from cardiometabolic diseases [6].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of non-alcoholic fatty liver disease (NAFLD) in the general population is growing worldwide: 44% in the USA, 33% in Europe and 25% in Italy [1][2][3][4][5][6]; for non-alcoholic steatohepatitis (NASH), the progressive form of NAFLD, the estimate is 2-3% [3,5]. A large cohort study reported that NAFLD was associated with 26% higher 5-year overall health-care costs, mainly from cardiometabolic diseases [6].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the prevalence is higher than 70% in subjects suffering from conditions associated with insulin resistance, such as obesity, type 2 diabetes, dyslipidemia, hypertension and MetS [13,14]. However, prospective cohort studies measuring the association between MetS and NAFLD in China's population are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses DOI: 10.1159/000497228 have reported the prevalence of NAFLD as 25.2% globally and 20.9% in the Chinese population [1,2], and NAFLD is recognized as a major current health burden. However, the pathogenesis of NAFLD remains unclear.…”
Section: Introductionmentioning
confidence: 99%